ANALISIS DPK, SUKU BUNGA, PENDAPATAN TERHADAP KREDIT MODAL KERJA PERBANKAN MASA PANDEMI - Oktaviana, Nurdiana Kholida (Contemporary Studies in Economic, Finance and Banking, 2022)
The purpose of this study was to determine the effect of the amount of Third Party Funds, Interest Rates and Income on Working Capital Loans at Commercial Banks During the COVID-19 Pandemic, both partially and simultaneously. The type of data used is secondary data obtained from annual data from Bank Indonesia Kediri during the COVID-19 pandemic from 2020 to 2021. The data analysis used is a regression analysis model with the F Test and T Test methods. The results of this study indicate that the Third Party Funds, interest rate and income variables simultaneously have a significant effect, and partially the Income variable does not have an significant effect on working capital loans at Banks General during the COVID-19 pandemic in Kediri City.